A novel pulse density modulation with semi-bridgeless active rectifier in inductive power transfer system for rail vehicle - Manyi Fan; Liming Shi; Zhenggang Yin; Yaohua Li (CES Transactions on Electrical Machines and Systems, 2017)
In this paper, a novel pulse density modulation (PDM) with semi-bridgeless active rectifier (S-BAR) in inductive power transfer (IPT) system for rail vehicle is proposed. It is to reduce switching losses of the active rectifier in pickups. In the control method, the insulated-gate bipolar transistors (IGBTs) in the S-BAR are controlled by synchronous PDM signals, so that zero-voltage switching (ZVS) and zero-current switching (ZCS) can be achieved in the whole output power range. The output power is regulated by changing the pulse density (PD) of the S-BAR since the it is almost linear proportional with the PD in high quality factor of pickup side. The communication device between the primary side and pickup side is not necessary anymore. The detailed theoretical analyses of the PDM method are provided, and its advantages are shown in a 7.5kW IPT prototype for rail vehicle. The experimental results are presented to verify the analysis and demonstrate the performance. The overall efficiency of the system by PDM control is 74.2% which is improved by 4% compared with phase shift (PS) control at light load.